(2 + 1)-Dimensional Coupled Model for Envelope Rossby Solitary Waves and Its Solutions as well as Chirp Effect. (18th October 2017) - Chen, Xin; Yang, Hongwei; Guo, Min; Yin, Baoshu
Abstract : Using the method of multiple scales and perturbation method, a set of coupled models describing the envelope Rossby solitary waves in (2 + 1 )-dimensional condition are obtained, also can be called coupled NLS (CNLS) equations. Following this, based on trial function method, the solutions of the NLS equation are deduced. Moreover, the modulation instability of coupled envelope Rossby waves is studied. We can find that the stable feature of coupled envelope Rossby waves is decided by the value of S . Finally, learning from the concept of chirp in the optical soliton communication field, we study the chirp effect caused by nonlinearity and dispersion in the propagation of Rossby waves.